Guardians under pressure, a spotlight on hypertension among healthcare workers in Kinshasa, Democratic Republic of Congo: a cross-sectional study - Rodrigue Khonde; Aline Labat; Joël Konde; Guillaume Kiyombo; Yves Coppieters (BMC, 2024)
Abstract Background Hypertension is one of the main risk factors for cardiovascular disease impacting over a billion people worldwide. Work environment factors could adversely affect workers' cardiovascular health, including contributing to hypertension. Healthcare workers who treat patients are also affected. In the Democratic Republic of Congo, limited studies explored the work environment factors associated with hypertension. This study aimed to examine hypertension prevalence and determine the associated risk factors among healthcare workers in Kinshasa. Methods A cross-sectional study was conducted in Kinshasa's healthcare facilities from December 2023 to January 2024 among healthcare workers selected by multistage stratified random sampling. Data was collected through a structured questionnaire using a modified WHO STEPwise approach and Karasek questionnaire. Anthropometric parameters, blood pressure, and fasting blood sugar were measured. The prevalence of hypertension was assessed. All sociodemographic, occupational, and lifestyle variables associated with hypertension were included in multivariable logistic regression analysis at the 5% significance level. Results The study encompassed 614 participants, comprising 55.2% females and 44.8% males. The mean age of participants was 38.8 ± 10.4 years, ranging from 20 to 78 years. The prevalence of hypertension was 22.6% and over half of those with hypertension (56.1%) were unaware of their condition. Of the known hypertensive participants before the study, 60.7% had uncontrolled blood pressure. In the multivariable analysis, identified risk factors for hypertension were age ≥ 40 years (aOR = 2.75, 95% CI: 1.64-4.61), seniority ≥ 10 years (aOR = 2.65, 95% CI: 1.54-4.58), multiple job holding (aOR = 3.11, 95% CI: 1.81-5.34), job stress (aOR = 1.84, 95% CI: 1.17-2.89), physical inactivity (aOR = 1.67, 95% CI: 1.03-2.68), overweight (aOR = 1.75, 95% CI: 1.06-2.90) and obesity (aOR = 3.75, 95% CI: 2.10-6.70). Conclusion Our results underline an important prevalence of hypertension among healthcare workers in Kinshasa, despite their medical knowledge of the causes and the risks. A healthy lifestyle among healthcare workers is fundamental for ensuring the efficiency and productivity of the healthcare system. Regulating multiple job holding and implementing a hypertension prevention intervention encompassing their holistic support is crucial for reducing job stress and promoting well-being.